Asynchronous Scheme for Optical Camera Communication-Based Infrastructure-to-Vehicle Communication - Trang Nguyen; Nam Tuan Le; Yeong Min Jang (International Journal of Distributed Sensor Networks)
This paper introduces infrastructure-to-vehicle (I2V) communication based on asynchronous optical camera communication (OCC), the transmitter of which can be an LED traffic light or electronic display, with the receiver being the existing front vehicle camera. In asynchronous OCC-based I2V communication, the key technique is an asynchronous scheme. An asynchronous scheme not only takes advantage of simplicity owing to the lack of an uplink or synchronization requirement, but is also the most feasible solution for communication to/from moving vehicles where synchronization is difficult to achieve within a short time. An asynchronous scheme for OCC-based I2V communication is proposed, and a performance evaluation shows its feasibility for use in a number of promising OCC-based wireless communication applications and services in a vehicular environment.